Ice-Binding Proteins in a Chrysophycean Snow Alga: Acquisition of an Essential Gene by Horizontal Gene Transfer - Raymond, James A.; Remias, Daniel (Frontiers in Microbiology, 2019)
All ice-associated algae examined so far have genes for ice-binding proteins (IBPs), which suggests that they are essential for survival in icy habitats. The most common type, type 1 IBPs, is also found in ice-associated bacteria and fungi. Previous studies have suggested that algal IBP genes were acquired by horizontal transfer from other microorganisms (probably bacteria). However, it remains unclear whether this is also the case for algae distantly related to the ones examined so far and whether microorganisms other than bacteria could be the donors. Furthermore, there is only limited evidence that these proteins are expressed at low temperature. Here, we show that Kremastochrysopsis austriaca (chrysophycea), an Austrian snow alga that is not closely related to any of the ice-associated algae examined so far, also produces IBPs, although their activity was weak. Sequencing its genome and the transcriptomes of cells grown at 1C and 15C revealed two isoforms of a type 1 IBP. In agreement with their putative function, the two isoforms were strongly upregulated by one and two orders of magnitude at 1C compared to 15C. In a phylogenetic tree, the K. austriaca IBPs were distant from other algal IBPs, with the closest matches being bacterial proteins. These results suggest that the IBPs were derived from a gene that was acquired from a bacterium unrelated to other IBP donor bacteria and confirm the essential role of algal IBPs.